Metode Pembelajaran Bahasa Arab di Sekolah Menengah Pertama - Agus Sya'roni (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
As Muslims, we should be familiar with Arabic. As we know, the beginning of the emergence of Islam came from the Arab Nation, even the holy book of Muslims is in Arabic. However, it is not the reason for us not to be able to master Arabic. Even make it as our everyday language. Arabic skills are speaking skills, able to listen well to be able to write and pronounce well too. Various attempts were made by the school to implement various Arabic learning methods. However, often learning Arabic, especially in junior high school, is deemed inadequate. There are many obstacles that are felt by educators, such as lack of awareness to learn Arabic, considering Arabic as a difficult language, and using inappropriate methods in their learning process. For these reasons, the author wants to make a simple effort with this simple writing to place a method that is in accordance with the timeliness of learning Arabic so that it is easily practiced by educators and easily accepted by students which expected that more awareness to use Arabic as every day language. An observation of the three methods to be analyzed, namely, qowaid and translation methods, direct methods, and eclectic methods.